Psychotropic-induced weight gain and telomere length: results from a one-year longitudinal study and a large population-based cohort - Marianna Piras; Jue Lin; Marie Catherine Sadler; Setareh Ranjbar; Claire Grosu; Nermine Laaboub; Martin Preisig; Franziska Gamma; Kerstin Jessica Plessen; Armin von Gunten; Philippe Conus; Zoltan Kutalik; et al. (Translational Psychiatry)
Abstract Weight-inducing psychotropic treatments are risk factors for age-related diseases such as cardiovascular disorders, which are associated with both inflammation and telomere length shortening. With a longitudinal design, the present study evaluates telomere length trajectories after 1 year of weight-inducing psychotropic medication, accounting for weight changes and the inflammatory biomarker high-sensitivity C-Reactive Protein (CRP). Among 200 patients, an overall median telomere shortening of -41.2 bp was observed (p = 0.014), which is comparable with the general population’s yearly telomere attrition. Linear regression showed on average -93.1 and -58.9 bp of further telomere shortening per five units of BMI for BMI values < or ≥30 kg/m2, respectively (p = 0.003 and p = 0.009, respectively). Importantly, the overall telomere shortening was predicted to be increased four-fold among patients with low baseline weight (i.e., 50 kg) and with clinically relevant weight gain (≥ 7%) after 1 year of treatment (interaction term between relevant weight gain and baseline weight: +6.3 bp, p = 0.016). Patients with relevant weight gain showed greater CRP levels (+ 49%; p = 0.016), and a telomere shortening of -36.2 bp (p = 0.010) was estimated whenever CRP level doubled. Mendelian randomization using UKBiobank data showed a causal effect of BMI on telomere shortening, notably stronger among patients receiving weight-inducing psychotropic treatments (n = 9798) than among psychiatric patients without such drugs (n = 16228) and non-psychiatric controls (n = 252932) (beta: -0.37, -0.12, -0.06, respectively; p = 0.004, p < 0.001, p < 0.001, respectively). Ultimately, telomere trajectories were associated with 1 year weight gain and increases in CRP levels, with telomere shortening strongly enhanced by BMI increments among patients receiving weight-inducing psychotropic treatments.